In Search for Awareness of the Needs: A study of an ESP Intensive Program for Government Official - Shu-Chuan Chen; Meng-Wei Mavise Lin (PAROLE: Journal of Linguistics and Education, 2022)
The study aims at constructing the awareness-building process of Taiwanese government officials from historical and sociocultural perspectives. This paper analyzes the program designed by Asia University which offered a 12-week intensive English training course for 19 government officials in Nantou in 2013. The study used: 1) Needs Analysis questionnaires (pre- and post- survey), and 2) structural interviews to discuss the following questions: 1) To what extent do officials enrolling the program actually need English in their works? 2) How do they realize their needs? 3) Based on the Needs Analysis (NA), what elements should a successful government ESP program incorporate? The study found that although participants agreed on the benefits of joining the program, not many of them know their specific needs. They just want to improve their English generally. However, they gradually notify that their needs as the program brought then district idea of learning. Finally, their replies suggested that more ESP for government officials are needed.